Effectiveness Test of Duck Mie (Innovation of Noodle-shaped Feed) on Peking Duck Productivity - Sukarne Sukarne; Muhammad Nursan (Jurnal Biologi Tropis, 2022)
Low feed efficiency is often an obstacle in duck farming business. The morphology of the duck's beak which is only suitable for muddy habitats causes ducks to be often inefficient in consuming feed in the form of mash, crumble or pellet. Thus, duck mie (a noodle-shaped and earthworm-like duck feed) has been innovated which is the natural food for ducks in their natural habitat (rice fields and swamp areas). The main ingredients for making duck mie are cheap and potential local ingredients, such as; golden snail, rice bran, corn flour and cassava flour. The purpose of this study was to determine the extent to which the provision of duck mie in the ration affects the productivity of Peking ducks. The method used in this study was a completely randomized design (CRD) using 4 treatments with 4 replications, the research material in the form of 80 DOD Peking ducks with treatment aged 1-7 days given 100% formulated feed. Age 8-14 days adapted to 95% formulated feed + 5% Duck Mie. Age 15 – 56 days given feed formulated according to treatment T0 = 100% formulated feed, T1 = 90% formulated feed + 10% Duck Mie, T2 = 80% formulated feed + 20% Duck Mie, and T3 = 70% formulated feed + 30 % Duck Mie. The data obtained then analyzed using analysis of variance (ANOVA), then tested using Duncan's Distance Test. The research parameters were feed intake, average daily gain (ADG), feed conversion ratio (FCR) and feed efficiency. Based on the study, it was found that the provision of duck mie in the ration did not show a significant effect (P<0.05) based on consumption, ADG, efficiency and feed conversion ratio of ducks.